O papel do fonoaudiólogo na rede de relações sociais de uma criança com Transtorno Global do Desenvolvimento: estudo de caso - Gertel, Marta Cecília Rabinovitsch (2008)
Introduction: In the field of Speech Therapy it is possible to find questionings on how our clinical intervention could facilitate the insertion of the individual, mainly patients with special needs. This way the context of speech therapy clinic could be directed to help the patient finding his own personal place, a fundamental aspect that will give him the sense of belonging both to his family and to school. The theoretical referential from Winnicott is the base of this research and it has been legitimated in various other researches from the speech therapy area in the sense of revealing ways to welcoming the patient, the complaint and the demand, understating through the therapeutic relation the needs and queries in the life of the individual who comes for treatment. It is important to stress that it is part of the clinic perspective the extension of care to the environment, in this case family and school, whenever necessary. Objective of this work: reflect and discuss the role of the speech therapist in conducting these therapeutic strategies during treatment of a child with Pervasive Developmental Disorder, mainly related to family and school. Methodology: This research is from a clinic-qualitative nature and was developed through a clinic case study of a child suffering from Pervasive Developmental Disorder. The material used was prepared from recorded reports and comprises the clinical material obtained on the family counseling from July 2002 to November 2004. The material cuts obtained portray the route followed through the patient story main point, stressing out significant moments that originated the development of the speech therapy therapeutic process regarding speech communication, social integration in the school and family environment. Results: The patient involved in this study attends normal classes and since speech therapy treatments, presented significant development in both social and family behavior, apart from showing an effective advance in oral communication. Conclusions: Assuming a perspective that leads the treatment to a child in a unique way, the therapeutic focus goes beyond clinic manifestations. To favor a physical and emotional environment able to promote constitutive experiences that respect the singularity of each patient taking into consideration the reality of the family and the community where the social nucleus is inserted. As a consequence ethnic identity, culture and ethics are better understood as fundaments of the human being and therefore as place of rooting and existence. In our understanding therefore the role of Phonoaudiology (speech therapy) could be directed to the creation of situations that will favor each patient process of inclusion in life, with all the respect that every one deserves